Political Revolutions in the Modern World - Shukhratovna, Jabbarova Sevara (Researchparks Publishing, 2023)
The main purpose of this article is the relevance of studying such a political phenomenon as revolution in the modern world, is related to their historical significance and role in the modern politics of various countries. Historically, many states have gone through revolutions in their development or their appearance is associated with revolutions. This article is devoted to revolutions in his decisions, that is, his final conclusions and methods.